Social and Emotional Learning Approaches to the Effectiveness of Da'wah for the Young Generation: A Study on Youth Coaches of the Lembang Grand Mosque, West Bandung Regency - Muhamad Hanif Fuadi; Frista Fitriany Ramadhanita; Aar Khariatul Maslamah (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
Da'wah for the younger generation faces big challenges in the fast-paced digital era. The Social and Emotional Learning (SEL) approach is an innovative alternative to increase the effectiveness of the delivery of religious values. This study aims to analyze the implementation of the SEL approach by youth coaches at the Lembang Grand Mosque, West Bandung Regency, in da'wah activities. The research method used is a case study with in-depth interviews and participatory observation of mosque coaches and adolescents. The results of the study show that the use of SEL elements such as empathy, social awareness, and emotion management is able to increase the acceptance of da'wah messages and encourage the active involvement of the younger generation in religious activities. Recommendations include intensive training for coaches to integrate SEL in da'wah and the development of SEL-based da'wah modules to support the sustainability of these activities.